Strategi Peningkatan Akreditasi Pusat Kegiatan Belajar Masyarakat (PKBM) dengan Pendekatan Interpretive Structural Modeling (ISM) - Putera, Hilmana Radhia; Ats-Tsauri, M. Ibrahim; Ropandi, Yaya (JURNAL TEKNIK INDUSTRI, 2022)
PKBM XYZ is a non-formal educational institution that received the recognition of C. This result illustrates that the quality assurance of education is still low there. This research aims to analyze PKBM's accreditation improvement strategy using the Interpretive Structural Modeling (ISM) approach so that it is known which accreditation instruments need to be prioritized for improvement to produce better education and accreditation at PKBM. The data collection method was carried out by distributing questionnaires to experts who are teachers and one of the founders of PKBM. Data analysis and processing using ISM equipped with MICMAC. The results of this study show that in order to improve accreditation at PKBM it is necessary to implement several activities: The first priority is to increase the points of educator experience and educator qualifications; The second priority is to increase the competence points of educators and the suitability of teaching materials; The third priority is to increase the number of learning methods.